Relationship Marketing as an Effective Strategy by Igbo Managed SMEs in Nigeria (Global Journal of Management and Business Research, 2013)
This paper contains the general introduction to our study. The research is expected to discuss the background of study which highlights what marketing and relationship marketing is, and its emergence as a strategy by Igbo SMEs in Nigeria. The research will go further to discuss our statement of problems, the research questions, research hypotheses, objectives of the study, significance and scope of the study, and the foreseeable limitations of the study. The significance and research questions form the basis of the hypotheses formulated. It reviewed the relevant literature in Relationship Marketing and Small Scale Industry in Nigeria. The Questionnaires analysed and conclusions are Reco-mmendations were made based on findings on the field such recommendations will help to improve the Roles that relationship marketing plays in the affairs of SME development in Nigeria.
Keywords: the research questions; research hypotheses; objectives of the study; significance and scope of the study; and the foreseeable limitations of the stud